Effects of energy drink consumption on electrocardiograph and photo plethysmograph - Md. Bashir, Uddina; Mohiuddin, Ahmada; Mohd Abdur, Rashid (Penerbit UTM Press, 2016)
The effects of energy drinks (ED) consumption on electrocardiograph (ECG) and photo plethysmograph (PPG) of several healthy human subjects are evaluated in this study. ECG recordings were performed with electrode lead set connected to MP36 (Biopac, USA) data acquisition unit. PPG recordings were also performed with pulse transducer connected to same data acquisition unit. ECG and PPG recordings were performed before and after having ED available in Bangladesh. Recordings were done with some interval of time from the instant of having ED. After consuming ED, it is observed that the R peak amplitude of ECG which is a vital part of QRS complex increases to a significant value. The maximum increment in R peak amplitude of ECG is found about 4.8% due to having ED which may give a short-term little boost of energy. This increment in R peak amplitude of ECG effectively continues up to 90 to 95 minutes approximately from the instant of being energized. A significant decrement is observed in peak to peak amplitude of PPG and heart rate (HR) due to the consumption of ED which may lead cardiac abnormality as well. Though the consumption of ED gives a short-term energy boost, it may cause any kinds of long-term cardiac diseases.